2017
DOI: 10.1186/s41043-017-0099-8
|View full text |Cite
|
Sign up to set email alerts
|

Partnering with women collectives for delivering essential women’s nutrition interventions in tribal areas of eastern India: a scoping study

Abstract: BackgroundWe examined the feasibility of engaging women collectives in delivering a package of women’s nutrition messages/services as a funded stakeholder in three tribal-dominated districts of Odisha, Jharkhand and Chhattisgarh States, in eastern India. These districts have high prevalence of child stunting and poor government service outreach.MethodsConducted between July 2014 and March 2015, an exploratory mix-methods design was adopted (review of coverage data and government reports, field interviews and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…Study in Malawi and Bangladesh reported that multi-sector cadres may provide essential elements such as high-quality facilitators for implementing and sustaining health services, high intervention coverage, timely intervention implementation, and supply-side interventions (Colbourn et al, 2013;Fottrell et al, 2013). Women in villages in India who engage and participate in group programs are more likely to use health facilities for maternal and delivery care, are better educated, and are better at addressing local challenges in the implementation of crucial nutrition interventions, according to research (HUNGaMa, 2011;Sethi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Study in Malawi and Bangladesh reported that multi-sector cadres may provide essential elements such as high-quality facilitators for implementing and sustaining health services, high intervention coverage, timely intervention implementation, and supply-side interventions (Colbourn et al, 2013;Fottrell et al, 2013). Women in villages in India who engage and participate in group programs are more likely to use health facilities for maternal and delivery care, are better educated, and are better at addressing local challenges in the implementation of crucial nutrition interventions, according to research (HUNGaMa, 2011;Sethi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Food‐based strategies such as incorporating traditional and indigenous foods (IFs) obtained locally from the natural environment through farming and wild harvesting can potentially improve dietary diversity and micronutrient deficiencies (Dwivedi et al, 2017; Sethi et al, 2017). Studies have shown a positive impact of production diversity on child anthropometric outcomes (Jones, 2017); better access to diverse and improved diets through home gardening and consumption of indigenous varieties of fruits and vegetables from forests and other nearby areas could likely improve micronutrient status (Berti, Krasevec, & FitzGerald, 2004; Girard, Self, McAuliffe, & Olude, 2012; Masset, Haddad, Cornelius, & Isaza‐Castro, 2012; Tontisirin, Nantel, & Bhattacharjee, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Among women’s agency indicators a relatively high proportion of mothers reported autonomy as well decision making authority, however, acceptance of domestic violence was quite high especially in Odisha and it did not vary much with SHG membership. In our earlier work we had noted that guarding women from domestic violence is critical for successful implementation of women’s centered livelihood programs [5]. The JEEViKA assessment also indicated that the program was successful in mobilizing marginalized women into institutional platforms, such women demonstrated higher levels of empowerment, when empowerment was measured by mobility, decision making and collective action [12].…”
Section: Discussionmentioning
confidence: 99%
“…It covers all the stages of a woman’s life-cycle with hightened nutritional vulnerability that is adolesence, pre-pregnancy (newlyweds), pregnancy and lactation (mothers of children under-two). Its design was informed by a scoping study that concluded that mature women’s Self- Help Groups (SHGs) and their federations also known as Village Organizations (VOs) and Cluster Level Federations (CLFs) have the potential to manage grants for improving last mile delivery of essential nutrition services for women, provided they are enabled, supervised and provided protection against domestic violence and exploitation [5]. The concept of layering nutrition interventions on economic empowerment programs for women is not new in the Indian context with programs like Kudumbashree and Andhra Pradesh Rural Poverty Reduction Program providing nearly two decades of learnings [6, 7].…”
Section: Introductionmentioning
confidence: 99%